Inaugural Archaeology Series. - Chia, Stephen (Penerbit USM, 2013)
This book discusses the wood coffin burial tradition in Kinabatangan Valley, Sabah. Archaeological evidence from past and recent studies has shown that Kinabatangan Valley was the centre of the wood coffin burial tradition in Sabah. Until now, many limestone caves and rockshelters containing hundreds of wood coffins have been found along the Kinabatangan River. Archaeological research and radiocarbon dating of the wood coffins suggested that the tradition of wood coffin burial in Kinabatangan Valley commenced as early as 1,000 years ago and is still being practised by the communities of Sungai.